Common Property and Social Capital Governance in the Context of the Cibulao Coffee Forest Farmers Group in Tugu Utara Village, Cisarua District, Bogor Regency - Saraan, Muhammad Imanuddin Kandias (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
This study aims to analyze the governance of common property and strengthening social capital in the Cibulao Coffee Forest Farmer Group (KTH) in Tugu Utara Village, Cisarua District, Bogor Regency. Using a qualitative approach with case studies, data were collected through in-depth interviews, participatory observations, and document studies. The results show that the synergy between collective ownership of forest resources and social capital based on trust, norms, and social networks creates a hybrid institution that supports sustainable forest management and community economic empowerment. However, this success is still limited to the micro scale and faces the risk of institutional exclusion if it is not integrated into the local political system in a participatory and strategic manner. David Easton's model and endogenous growth theory are used to map the challenges and opportunities for the long-term sustainability of the Cibulao Coffee KTH.